"Managed competition" for Ireland? The single versus multiple payer debate. - RYAN, PADHRAIG (My University, 2014)
Background A persistent feature of international health policy debate is whether a single-payer or multiple-payer system can offer superior performance. In Ireland, a major reform proposal is the introduction of ‘managed competition’ based on the recent reforms in the Netherlands, which would replace many functions of Ireland’s public payer with a system of competing health insurers from 2016. This article debates whether Ireland meets the preconditions for effective managed competition, and whether the government should implement the reform according to its stated timeline. We support our arguments by discussing the functioning of the Dutch and Irish systems. Discussion Although Ireland currently lacks key preconditions for effective implementation, the Dutch experience demonstrates that some of these can be implemented over time, such as a more rigorous risk equalization system. A fundamental problem may be Ireland’s sparse hospital distribution. This may increase the market power of hospitals and weaken insurers’ ability to exclude inefficient or poor quality hospitals from contracts, leading to unwarranted spending growth. To mitigate this, the government proposes to introduce a system of price caps for hospital services. The Dutch system of competition is still in transition and it is premature to judge its success. The new system may have catalyzed increased transparency regarding clinical performance, but outcome measurement remains crude. A multi-payer environment creates some disincentives for quality improvement, one of which is free-riding by insurers on their rivals’ quality investments. If a Dutch insurer invests in improving hospital quality, hospitals will probably offer equivalent quality to consumers enrolled with other insurance companies. This enhances equity, but may weaken incentives for improvement. Consequently the Irish government, rather than insurers, may need to assume responsibility for investing in clinical quality. Plans are in place to assure consumers of free choice of insurer, but a key concern is a potential shortfall of institutional capacity to regulate managed competition. Summary Managed competition requires a long transition period and the requisite preconditions are not yet in place. The Irish government should refrain from introducing managed competition until sufficient preconditions are in place to allow effective performance.
PUBLISHED
Keywords: Managed competition; Quality; Performance measurement; Market structure; Financing reform; Ireland; Netherlands; Health insurance